Scrub typhus infection, not a benign disease: an experience from a tertiary care center in Northern India - Jain, Deepak (Med Pharm Rep, 2019)
INTRODUCTION: Scrub typhus is an acute febrile illness caused by Orientia tsutsugamushi. It is characterised by fever, rash, myalgia and diffuse lymphadenopathy. Most common complications are sepsis, shock, acute respiratory distress syndrome (ARDS), hepatitis, pre renal azotemia and multi organ dysfunction syndrome (MODS). Mortality rates range from 7–30% in untreated cases. Scrub typhus is endemic to a part of the world known as ‘the tsutsugamushi triangle’. River banks, grassy areas generally harbour scrub typhus infection; however, recently there has been an increase in prevalence of infection from dry regions like Haryana. OBJECTIVE: To assess the clinical spectrum and complications of scrub typhus infection at a tertiary care centre in North India. MATERIAL AND METHODS: An observational study was conducted on patients >14 years old with acute febrile illness >7 days duration, admitted indoor from emergency department, from July to November 2017. Suspected cases were tested for specific IgM antibodies against Orientia tsutsugamushi by ELISA. RESULTS: Among the 230 patients, screened for scrub typhus infection, 39 (16.95%) came out to be positive. Most common patient complaints were fever followed by cough and breathlessness, myalgia, nausea, vomiting and behavioral abnormality. 15% of patients required inotropic support initially and 48% had oxygen saturation of less than 90% at the time of presentation. Pleural effusion and crepitations were present in 41% of patients. Most common biochemical alterations were: abnormal liver function tests (95%), followed by thrombocytopenia, anemia, abnormal renal function tests, and hyponatremia. 12 patients (30.7%) were shifted to intensive care unit, 8 of which (20.5%) needed invasive mechanical ventilation and 4 patients (10.3%) underwent hemodialysis. Various complications were noted in 89.7% of cases, the most common being ARDS followed by sepsis, acute kidney injury (AKI) and meningitis. The mortality rate in this study was 18%. CONCLUSIONS: This study emphasizes that scrub typhus infection is on a rampant resurgence and it is associated with significant complications. High degree of suspicion as well as development of effective measures to treat, control and prevent is critical to lower the disease burden.